Inhibition of Human Platelet Functions by Verapamil - Ikeda, Y; Kikuchi, M; Toyama, K; Watanabe, K; Ando, Y (Thrombosis and Haemostasis, 1981)
The effects of verapamil, a coronary vasodilator, on platelet functions were studied.Platelet aggregation induced by ADP, epinephrine or collagen was inhibited by verapamil in vitro. Calcium ionophore A23187-induced platelet aggregation was also inhibited by verapamil in a concentration dependent manner. In washed platelets, verapamil caused a dose-dependent inhibition of serotonin release induced either by thrombin or A23187 in the absence of extracellular calcium. Addition of 1 mM CaCl2 with A23187 or thrombin partially overcame this inhibition. Addition of 1 mM CaCl2 in the absence of verapamil had no effect on thrombin- or A23187-induced secretion. When verapamil was administered to the healthy volunteers at the dosage commonly used, inhibition of platelet aggregation was observed 2 hrs after the drug ingestion. It is of great interest that verapamil potentiated the anti-aggregating activity of prostacyclin in vitro.Our results may suggest a potential role for verapamil in the treatment of thrombotic disorders.
Keywords: Verapamil; Calcium antagonist; Platelet function; Anti-platelet agent